Correction notices in psychology: impactful or inconsequential? - Heyman, Tom (R Soc Open Sci, 2020)
Science is self-correcting, or so the adage goes, but to what extent is that indeed the case? Answering this question requires careful consideration of the various approaches to achieve the collective goal of self-correction. One of the most straightforward mechanisms is individual self-correction: researchers rectifying their own mistakes by publishing a correction notice. Although it offers an efficient route to correcting the scientific record, it has received little to no attention from a metascientific point of view. We aim to fill this void by analysing the content of correction notices published from 2010 until 2018 in the three psychology journals featuring the highest number of corrections over that timespan based on the Scopus database (i.e. Psychological Science with N = 58, Frontiers in Psychology with N = 99 and Journal of Affective Disorders with N = 57). More concretely, we examined which aspects of the original papers were affected (e.g. hypotheses, data-analyses, metadata such as author order, affiliations, funding information etc.) as well as the perceived implications for the papers’ main findings. Our exploratory analyses showed that many corrections involved inconsequential errors. Furthermore, authors rarely revised their conclusions, even though several corrections concerned changes to the results. We conclude with a discussion of current policies, and suggest ways to improve upon the present situation by (i) preventing mistakes, and (ii) transparently rectifying those mistakes that do find their way into the literature.